INTELLECTUAL BARRIER IN COMMUNICATION - Kugai, Kseniia (Collection of scientific papers «ΛΌГOΣ», 2023)
Communication, relationships between people is not just an exchange of information. It involves mutual partners’ activity, interaction. Any interaction is impossible without mutual understanding. At the same time, it is very important how the communication partner is perceived.